Crenças linguísticas e a realidade da sala de aula: propostas sociolinguísticas para o ensino de língua portuguesa no nono ano do ensino fundamental - Frasson, Carla Beatriz (2016)
The study of linguistic attitudes and beliefs has been expanding in recent years and has much to contribute to the improvement of Portuguese language teaching, especially in the country's public schools, since social and economic diversity is more noticeable in this context of teaching when Compared to private schools. The analysis of linguistic attitudes and beliefs is of great importance in the study of the teaching / learning process of the Portuguese language, because studying the beliefs and their consequent attitudes shows to the teacher what are the stimuli that guide (and possibly, the opposite also applies) The students in relation to the teaching of the mother tongue, mainly the learned norm. In this sense, based on the assumption that the effective knowledge of the cultured norm is of utmost importance to the speaker in the society in which he lives, without, however, depreciating the linguistic variations he uses, we believe that a school, Their social role in providing the conditions for students to develop their oral and written language skills, should work not only on the most prestigious varieties but also on varieties that are often stigmatized by most of society and which are often Used by students. This is of great relevance for an effective and complete teaching of the Portuguese language to its native speaker, since such varieties (those of nonprestige) characterize their identity. It is necessary that the school works with the students the importance of the teaching of the mother tongue and its contextualization with the reality that surrounds them, highlighting the value that has the variety used by them and in which situations it is convenient to use this variety. Thus, the work that the school must follow requires, above all, to deepen the study of the linguistic beliefs that involve the students in the language learning. After all, the study of beliefs provides teachers with the necessary foundation to place the student as an important actor in pedagogical practice and to investigate their beliefs about language. In this dissertation, we will investigate, in the light of the sociolinguistic knowledge of researchers such as Madeira (2005), Cyranka (2007), Faraco (2008), Bagno (2011) and Bortoni-Ricardo (2004). The beliefs that the students bring with them regarding the teaching of Portuguese language, through the application and analysis of questionnaires of beliefs and linguistic attitudes. In addition to the questionnaire, we also analyzed the textbooks worked in the schools surveyed, observing if they are consonant with the postulate in the National Curricular Parameters, mainly in what refers to the concern in making possible a teaching based on the new discoveries of the language and, consequently, in the recognition of the character Heterogeneous language. Reflecting on these issues and considering the absence, in the textbooks analyzed, of exercises that actually consider issues related to the cultural and linguistic diversity that make up the scenario of Brazilian classrooms, especially in public contexts of education, we propose, finally, , A workbook in which exercises are suggested that focus mainly on the study of cohesive links